Process development for 6-aminopenicillanic acid production using lentikats-encapsulated escherichia coli cells expressing penicillin V acylase - Sawant, Amol M.; Sunder, Avinash Vellore; Vamkudoth, Koteswara Rao; Ramasamy, Sureshkumar; Pundle, Archana (ACS Omega, 2020)
Penicillin V acylase (PVA, EC 3.5.1.11) hydrolyzes the side chain of phenoxymethylpenicillin (Pen V) and finds application in the manufacture of the pharmaceutical intermediate 6-aminopenicillanic acid (6-APA). Here, we report the scale-up of cultivation of Escherichia coli whole cells expressing a highly active PVA from Pectobacterium atrosepticum and their encapsulation in polyvinyl alcohol-poly(ethylene glycol) Lentikats hydrogels. A biocatalytic process for the hydrolysis of 2% (w/v) Pen V was set up in a 2 L reactor using the Lentikats-immobilized whole cells, with a customized setup to enable continuous downstream processing of the reaction products. The biocatalytic reaction afforded complete conversion of Pen V for 10 reaction cycles, with an overall 90% conversion up to 50 cycles. The bioprocess was further scaled up to the pilot-scale at 10 L, enabling complete conversion of Pen V to 6-APA for 10 cycles. The 6-APA and phenoxy acetic acid products were recovered from downstream processing with isolated yields of 85-90 and 87-92%, respectively. Immobilization in Lentikats beads improved the stability of the whole cells on storage, maintaining 90-100% activity and similar conversion efficiency after 3 months at 4 degrees C. The robust PVA biocatalyst can be employed in a continuous process to provide a sustainable route for bulk 6-APA production from Pen V.